The Effect of Age on Improvements in Vestibulo-Ocular Reflexes and Balance Control after Acute Unilateral Peripheral Vestibular Loss - Scheltinga, Alja; Honegger, Flurin; Timmermans, Dionne P. H.; Allum, John H. J. (Frontiers in Neurology, 2016)
Background An acute unilateral peripheral vestibular loss (aUVL) initially causes severe gaze and balance control problems. However, vestibulo-ocular reflexes (VOR) and balance control are nearly normal 3 months later as a result of peripheral recovery and/or central compensation. As pre-existing vestibular sensory loss is assumed to be greater in the healthy elderly, this study investigated whether improvements in VOR and balance function over time after aUVL are different for the elderly than for the young. Methods Thirty aUVL patients divided into three age-groups were studied (8 age range 23–35, 10 with range 43–58, and 12 with range 60–74 years). To measure VOR function eye movements were recorded during caloric irrigation, rotating chair (ROT), and head impulse tests. Balance control during stance and gait was recorded as lower trunk angular velocity in the pitch and roll planes. Measurements were taken at deficit onset, and 3, 6, and 13 weeks later. Results There was one difference in VOR improvements over time between the age-groups: Low acceleration ROT responses were less at onset in the elderly group. Deficit side VOR responses and asymmetries in each group improved to within ranges of healthy controls at 13 weeks. Trunk sway of the elderly was greater for stance and gait at onset when compared to healthy age-matched controls and the young and greater than that of the young and controls during gait tasks at 13 weeks. The sway of the young was not different from controls at either time point. Balance control for the elderly improved slower than for the young. Conclusion These results indicate that VOR improvement after an aUVL does not differ with age, except for low accelerations. Recovery rates are different between age-groups for balance control tests. Balance control in the elderly is more abnormal at aUVL onset for stance and gait tasks with the gait abnormalities remaining after 13 weeks. Thus, we conclude that balance control in the elderly is more affected by the UVL than for the young, and the young overcome balance deficits more rapidly. These differences with age should be taken into account when planning rehabilitation.